The influence of the river runoff in the artisanal fisheries catches in tropical coastal waters: The case of the Zambezi River and the fisheries catches in the northern Sofala Bank, Mozambique - Hoguane,Antonio Mubango (2015)
The artisanal catches contributes significantly in the overall annual fish production in Mozambique, estimated to 115,000 -140,000 tones, and thus of significant importance to livelihood of the coastal communities. However, the variation in fish production depends on several factors, among which the climatic factors, that need to be understood for sustainable fisheries management. The present study analyses the influence of the river runoff in coastal fisheries production, using the Zambezi Runoff (1996-2014) as a climatic indicator and the artisanal fisheries catches (2000-2014) as the indicator of fisheries production. The results obtained indicated that the artisanal catches in Sofala Bank were dominated by resident species in the region of fresh water influence (Engraulidae (53%), Clupeídea (10%), Sciaenidae (8%) and Sergestidae (7%)), by species that inhabit these regions at their earlier stage of life (Penaeidae (4%)) and by species that inhabit the vicinity and move to the region of fresh water influence for feeding (Trichiuridae (6%), Ariidae (4%), Carangidae (4%) and Hemulidae (2%)); The total annual catches were positively-linearly correlated with the total annual runoff (slope = 0.343, r² = 0.500, p = 0.005, n = 14). Further, the catches correlated better with both the wet season runoff (slope = 0.534, r² = 0.369, p = 0.021, n = 14) and the dry season runoff (slope = 0.773, r² = 0.389, p = 0.013, n = 15). The result is justified by the fact that most of the species caught (Engraulidae, Clupeídea, Sergestidae and Penaeidae) live in the region of freshwater influence, with one to two years life span and recruited to fisheries within the first year of their life. The present study emphasises the importance of the environmental/climatic factors such as river runoff in the fish production, and hence, on the need for the inclusion of the runoff variability in the fisheries management strategies.